Pengaruh Lingkungan Kerja dan Komunikasi Terhadap Kepuasan Kerja Pegawai Dinas Pendidikan Kota Medan - Mutholib Mutholib (UMSU, 2023)
The purpose of this research is to determine the influence of the Work Environment and Communication on Job Satisfaction at Medan City Education Service Employment. The data collection method in this research is through field analysis techniques or surveys by distributing questionnaires. The samples taken in this research were employees of the Medan City Education Department, totaling 72 employees. The data analysis technique used to determine the influence of related variables is using classical assumption test techniques, multiple linear regression, T test (partial), F test (simultaneous), and coefficient of determination. The results of the analysis show that there is a positive and significant influence between variable Variable This means that the work environment and communication have a significant influence on the job satisfaction of Medan City Education Department employees.